2015
DOI: 10.6061/clinics/2015(01)06
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological differences between septic arthritis of the knee and hip caused by oxacillin-sensitive and -resistant s. aureus

Abstract: OBJECTIVE:To establish the risk factors for joint infection by oxacillin-resistant Staphylococcus aureus (MRSA) using clinical and epidemiological data.METHODS:All septic arthritis cases of the knee and hip diagnosed and treated in our institution from 2006 to 2012 were evaluated retrospectively. Only patients with cultures identified as microbial agents were included in the study. The clinical and epidemiological characteristics of the patients were analyzed, seeking the differences between populations affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…The most common causative agent associated with septic arthritis is S. aureus , which accounts for about 50% of cases [ 43 ]. Recently, an increase in methicillin-resistant S. aureus (MRSA) infections has been reported in several health-care systems, particularly in the elderly and intravenous drug abuser populations as well as in patients who underwent orthopedic procedures [ 44 ]. MRSA has been associated with 18% and 41% of septic arthritis cases in studies in São Paulo, Brazil and Tainan, Taiwan, respectively [ 44 , 45 ].…”
Section: Septic Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…The most common causative agent associated with septic arthritis is S. aureus , which accounts for about 50% of cases [ 43 ]. Recently, an increase in methicillin-resistant S. aureus (MRSA) infections has been reported in several health-care systems, particularly in the elderly and intravenous drug abuser populations as well as in patients who underwent orthopedic procedures [ 44 ]. MRSA has been associated with 18% and 41% of septic arthritis cases in studies in São Paulo, Brazil and Tainan, Taiwan, respectively [ 44 , 45 ].…”
Section: Septic Arthritismentioning
confidence: 99%
“…Recently, an increase in methicillin-resistant S. aureus (MRSA) infections has been reported in several health-care systems, particularly in the elderly and intravenous drug abuser populations as well as in patients who underwent orthopedic procedures [ 44 ]. MRSA has been associated with 18% and 41% of septic arthritis cases in studies in São Paulo, Brazil and Tainan, Taiwan, respectively [ 44 , 45 ]. Other bacteria such as group B streptococci, Streptococcus pneumoniae , Neisseria gonorhoeae , Pseudomonas aeruginosa , Escherichia coli , Proteus genus and Klebsiella species can be associated with septic arthritis, but are less frequent [ 46 ].…”
Section: Septic Arthritismentioning
confidence: 99%
“…The only analyzed parameter that differed significantly was the patient history in that a history of a health service-related environmental encounter was associated with infection due to S. aureus. The growing incidence of methicillin-resistant S. aureus likely explains these findings 19. Some authors have suggested that in patients relating a health service environmental exposure, vancomycin or teicoplanin should be considered the first-choice empirical antibiotics 19.…”
Section: Discussionmentioning
confidence: 99%
“…The growing incidence of methicillin-resistant S. aureus likely explains these findings 19. Some authors have suggested that in patients relating a health service environmental exposure, vancomycin or teicoplanin should be considered the first-choice empirical antibiotics 19. Patients with S. aureus -related infections also tended to have higher CRP values and shorter intervals between symptom onset and the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Vardakas et al found that CA-MRSA bone and joint infections mainly affect patients younger than 2 years of age and African Americans e the reasons for this are not clear and it may be related to access to care or atypical presentations of bone and joint infections in very young children [19]. For patients with septic arthritis of the hip or knee, if a patient were from a health-service-related environment, this was associated with an infection by MRSA more than that of a methicillin-sensitive S. aureus [20].…”
Section: Microbiologymentioning
confidence: 97%